Multiple, not single, recipient muscle tendon transfers produce well-coordinated thumb-tip movement in lateral pinch grasp: a simulation study with application to restoration of improved grasp after tetraplegia - Smith, Cole D.; Towles, Joseph D. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTendon transfer surgeries that engage the flexor pollicis longus (FPL) muscle are commonly performed to enable lateral pinch grasp in persons with tetraplegia. Functional outcomes, however, have been mixed. This may be the case, in part, because the FPL produces hyperflexion at the interphalangeal (IP) joint and radial deviation at the carpometacarpal (CMC) joint. Therefore, the goal of this simulation study was to investigate whether small groups of muscles could produce movement with less IP joint hyperflexion and CMC joint ab/adduction than the FPL produces during lateral pinch grasp.MethodsWe adapted a published, open-source computational musculoskeletal model of the hand to simulate lateral pinch grasp movement. A forward dynamics simulation approach was used to drive the thumb, with 27 muscle groups being considered, from an extended posture to a flexed posture to make contact with the side of the index finger. We calculated CMC joint ab/adduction deviation from the flexion–extension plane and IP joint flexion in the plane that all muscle groups produced and compared those joint angle movements to those of the FPL when it alone drove the thumb.ResultsOf the 27 simulations, three muscle groups, each consisting of three or four muscles, generated lower IP joint flexion and CMC joint ab/adduction compared with the FPL.ConclusionThis study points to the potential of novel, multiple recipient muscle tendon transfer surgeries to outperform the current standard of care to restore lateral pinch grasp following tetraplegia.